(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
Medical, psychological and pedagogical disciplines consider childhood as a crucial period for the future development of children as individuals and as citizens. Children acquire family values and morals from their parents, thus in order to have a healthy and non-violent society, well-being must be initially sought in the family. Unfortunately, redundant, children are often the victims of various forms of violence within the family. In particular, sexual abuse within the family - namely incest - is considered to be the most serious form of violence/abuse which negatively affects, with long-term consequences, the well-being, growth and the proper psycho-physical development of the child. In this paper the authors will approach the treatment of the phenomenon of incest in cases where the victims are children. Incest as a multidimensional phenomenon, in this paper will be treated in both criminal and family legal terms. In the criminal aspect, we will treat the criminal offense of incest as incriminated in the Criminal Code of the RNM. In particular, the authors will elaborate the connection between pedophilia as a mental disorder and the criminal offense of incest when the victims are children. Meanwhile, from the family legal perspective, the importance of respecting close blood relatives will be treated as a relationship that is created between two or more persons, who are descending from each other or are descending from a common ancestor. In this section authors emphasize the importance of understanding genetic origin for children conceived with donated genetic material and adopted children in order to prevent incestuous relationships between close blood relatives.